The politics of urban governance - Pierre, Jon. 4 0 16; 5 (Houndmills, Basingstoke, Hampshire : Palgrave Macmillan, 2011)
This broad ranging new text analyses the emerging shape of urban politics in the twenty-first century. The author identifies 4 main models of urban governance--management, Corporatist. Pro-Growth and Welfare--and assesses their different implications for the major issues, interests and problems in the contemporary urban arena--
Machine generated contents note: -- The Challenge of Urban Governance * Rethinking the Local State * The Managerial City * The Corporatist City * The Pro-Growth City * The Welfare City * The Decline of Urban Politics? * Cities in Global Governance * Conclusion: The Future of Urban Politics.
Includes bibliographical references and index.
Keywords: 2 -- 0; 6; Cross-cultural studies. -- Municipal government;Local government;Political leadership;Sociology, Urban;Urban policy -- 20 -- Cross-cultural studies.;Cross-cultural studies.;Cross-cultural studies.;Cross-cultural studies; 20; 2